2016
DOI: 10.1177/1029864916634420
|View full text |Cite
|
Sign up to set email alerts
|

Changes in motivation as expertise develops: Relationships with musical aspirations

Abstract: Recent models of musical motivation have recognised the complex interactions which occur between environmental (cultural, institutional, familial, educational) and internal factors (cognition and affect) in enhancing or reducing motivation. Much previous research has been small scale and not taken account of long term musical aspirations. This paper aims to address these issues exploring changes in motivation as expertise develops with a large sample of learners. 3325 young musicians, aged 6-19 playing a wide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 73 publications
2
32
0
1
Order By: Relevance
“…Given these responses, it is not surprising that only 55% indicated that they thought that they were a musical person. This suggests that while the Musical Futures approach had enhanced interest for a substantial proportion of students, many had failed to develop an identity as a musician, a crucial factor in maintaining engagement with music throughout the lifespan (Hallam et al, 2015). This reflects the evidence from the Nordic research which reported that some students' needs were not being met (Bergman, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Given these responses, it is not surprising that only 55% indicated that they thought that they were a musical person. This suggests that while the Musical Futures approach had enhanced interest for a substantial proportion of students, many had failed to develop an identity as a musician, a crucial factor in maintaining engagement with music throughout the lifespan (Hallam et al, 2015). This reflects the evidence from the Nordic research which reported that some students' needs were not being met (Bergman, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Both of these regulations have low levels of autonomy and, thus, may promote conformity, thwart self-expression, and result in feelings of alienation and motivation of lesser quality [16]. Nevertheless, as people progress through their careers in music, the proportions of diverse intrinsic and extrinsic motives may vary: for instance, motives like expressing a musical identity, satisfying personal needs, approaching learning effectively, or addressing specific environmental conditions may, respectively, gain more salience during specific periods, consequently, affecting motivation and possibly even individual career trajectories [26]. Students' experiences may vary not only due to the specific moment in their music career, but also students with different motivational goals may experience their learning environments differently, because they direct their attention to different aspects [27].…”
Section: Psychological Needs Satisfaction and Behavioural Regulationsmentioning
confidence: 99%
“…Many years of training and preparation are required to acquire such skills and put these into practice, a process that involves not only the development of technical dexterity, but also the ability to regulate one's learning activity and to control emotional factors (Hallam, 2002). Personal motivation and the context in which learning takes place also exert a pivotal influence throughout this entire process (Moore et al, 2003;Creech and Hallam, 2011;Lehmann and Kristensen, 2014;Hallam et al, 2016).…”
Section: Introduction and Rationalementioning
confidence: 99%